The Colony of New York - Whitehurst, Susan (New York The Rosen Publishing Group,Inc, 2000)
Relates the history of the colony of New York from its founding by the Dutch in 1609 to statehood in 1788.
Keywords: New York (State) - History - Colonial period, ca. 1600-1775.; New York (State) - History - 1775 - 1865.; Series: The library of the thirteen colonies and the lost colony